Deciphering Late Quaternary stratigraphy in a marine setting using CPTu data: insights from Northern Fujian, China - Yufeng Chen; Xianbiao Wang; Yanjun Tian; Weijun Zheng; Yuanyuan Chen; Shihao Liu (Frontiers in Marine Science, 2026)
The Late Quaternary stratigraphy of the inner shelf along the southeastern China coast remains poorly resolved because of the reliance on sparse borehole data. Here, we integrate 54 downhole CPTu soundings with borehole logs achieving penetration of ~110 m, together with a ~78 m sediment core (LJ01) recovered from the offshore area in Northern Fujian, capturing a near-complete, high-resolution stratigraphic record. The calibrated CPTu responses enable robust facies discrimination and reveal three vertically stacked successions that define the regional stratigraphic architecture in the Xiapu offshore area. Succession 1 (MIS 6–5) is dominated by fluvial channel belts overlain by an aggrading floodplain system, recording a transition from sediment bypass to increased accommodation. Succession 2 (MIS 4–3) comprises fluvial–tidal river deposits passing upward into transitional floodplain–tidal flat and estuarine bay facies, reflecting increasing marine influence during relative sea-level rise. Succession 3 (MIS 2–1) is characterized by transgressive reworked deposits capped by offshore/prodelta sedimentation, indicating the establishment of inner-shelf conditions during the Holocene transgression. This stratigraphic organization links facies stacking directly to glacio-eustatic cycles and demonstrates that calibrated CPTu datasets can resolve long, continuous subsurface records in data-limited inner shelf settings, providing a transferable framework for Late Quaternary coastal stratigraphic analysis.